2010
DOI: 10.1007/s13277-010-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma antigen 1 and 2 expression in cultured normal peripheral blood mononuclear cells and in vulvar squamous cell carcinoma

Abstract: Squamous cell carcinoma antigen (SCCA) is expressed in normal squamous cell epithelia and in squamous cell carcinomas (SCC). Two nearly identical genes encode the inhibitory serpins SCCA1 (SERPINB3) and SCCA2 (SERPINB4). Serum levels of SCCA are elevated in patients with benign skin diseases and in patients with SCC. SCCA, used for the monitoring of SCC patients, presents no satisfactory diagnostic specificity. As we have shown previously, the reverse transcription polymerase chain reaction (RT-PCR)-based SCCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The biological role of this serpin has not been yet completely defined. SB3 is physiologically expressed in squamous epithelia, in endothelial cells of the veins, in arteries walls9 and in peripheral blood mononuclear cells10. It is also overexpressed in neoplastic cells of epithelial origin1112.…”
mentioning
confidence: 99%
“…The biological role of this serpin has not been yet completely defined. SB3 is physiologically expressed in squamous epithelia, in endothelial cells of the veins, in arteries walls9 and in peripheral blood mononuclear cells10. It is also overexpressed in neoplastic cells of epithelial origin1112.…”
mentioning
confidence: 99%
“…However, Spi2A can be induced by IFN-γ in activated macrophages 43 and so it is possible that in different physiological settings IFN-γ may affect Th1 cell survival through Spi2A up-regulation. SCCA-1/SCCA-2 expression has been noted previously in human mononuclear cells 45 and intriguingly it has been reported that deficiency in mouse Serpinb3a , which is thought to be the homologue of human SCAA-1/SCAA-2, reduces airway hyper-responsiveness by limiting goblet cell hyperplasia 46 . In contrast to our findings with OVA-specific IgE levels in our Serpina3g (Spi2A) KO mouse, levels of HDM-specific IgG1 and IgE l were no different between Serpinb3a KO and wild-type mice 46 .…”
Section: Discussionmentioning
confidence: 72%
“…The over-expression of SCCA was initially described in many different cancers of epithelial origin such as head and neck, vulvar, lung and oesophageal tumors [13][14][15][16]. Recently Pontisso et al [17] detected SCCA expression in HCC by immunohistochemistry for the first time but the expression pattern of SCCA1 and SCCA2 in cancer pathogenesis is not fully defined.…”
mentioning
confidence: 99%